Effect of Some Plant Part Extracts in Management of Seed Borne Pathogens - Sangvikar, Roopa V. (Asian Journal of Biological and Life Sciences, 2012)
Plant disease causing pathogens are mostly seed borne and seed transmitted. Seed borne pathogens cause diseases of seed, seedling, and adult plants at various growth stages. Seeds are treated by various means to get rid of such pathogens, physical, chemical, and biological methods are available for treatment. Biological method need preference since plant metabolites and plant based pesticides appear to be one of the better alternatives as they are known to have minimal environmental impact and danger to consumers in contrast to synthetic pesticides. Exploitation of plant metabolites in crop protection and prevention of biodeterioration caused by fungi appear to be promising. In view of these the present investigation has to be undertaken to screen some plant extracts against seed borne pathogenic fungi .The purpose of investigation is to search for alternative approach to prevent bio deterioration of seeds in an ecofriendly way.